The Effectiveness of Leadership Ethics in Improving Teacher’s Working Relations at SDN 112323 Silumajang - Syafri Fadillah Marpaung; Adilla Aisyahrani; Khoirunnisa Fadila Rambe; Lilis Astika; Nurul Sufni (Edumaspul: Jurnal Pendidikan, 2023)
Leadership ethics or the role of the principal in carrying out his duties and responsibilities has a significant impact on the success of the principal's effectiveness in strengthening working relationships with educators or teachers, with the aim of improving their performance in the school environment. The positive attitude shown by the school principal can create a comfortable working atmosphere and increase motivation among teaching staff. As a result, teachers will consciously improve themselves and achieve optimal performance in carrying out their duties. Improving teacher performance not only benefits the individual, but also has a positive impact on the overall performance of the school. Therefore, school principals need to demonstrate integrity and good moral behavior in the school environment. The main focus of this research is to evaluate the effectiveness of ethical leadership in strengthening working relationships between leaders and teachers, as well as among fellow teachers or teaching staff. This research was specifically conducted at SD Negeri 112323 Silumanjang School, using a qualitative approach. Data was collected through observation, in-depth interviews, and analysis of written documents. It is hoped that the results of this research can contribute as a source of theory or reference for improving working relationships with teachers, especially in the context of improving the quality of educational institutions.